2010
DOI: 10.1128/aem.00180-10
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations between the Microbiotas in the Litter and in the Intestines of Commercial Broiler Chickens

Abstract: The intestinal microbiota of broiler chickens and the microbiota in the litter have been well studied, but the interactions between these two microbiotas remain to be determined. Therefore, we examined their reciprocal effects by analyzing the intestinal microbiotas of broilers reared on fresh pine shavings versus reused litter, as well as the litter microbiota over a 6-week cycle. Composite ileal mucosal and cecal luminal samples from birds (n ‫؍‬ 10) reared with both litter conditions (fresh versus reused) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
126
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(141 citation statements)
references
References 42 publications
9
126
1
5
Order By: Relevance
“…It should be noted that the broiler litter is primarily a mixture of bedding materials and bird excreta, and the management of litter varied from feedlot to feedlot. With continued reuse, the litter environment becomes more complex, 57 which may have a profound impact on distribution of antibiotic resistant bacteria (ARB) and ARGs in litter and even the subsequent litterapplied soils.…”
Section: Dissemination Of Args In the Broiler Feedlotsmentioning
confidence: 99%
“…It should be noted that the broiler litter is primarily a mixture of bedding materials and bird excreta, and the management of litter varied from feedlot to feedlot. With continued reuse, the litter environment becomes more complex, 57 which may have a profound impact on distribution of antibiotic resistant bacteria (ARB) and ARGs in litter and even the subsequent litterapplied soils.…”
Section: Dissemination Of Args In the Broiler Feedlotsmentioning
confidence: 99%
“…Cressman et al reported that used litter produced more Clostridia within the ileum while fresh litter produced more environmental Lactobacillus [13]. In this study, we used molecular ecology to evaluate the composition of broiler litter over multiple flock cycles in order to reveal the effects of using antibiotic alternatives.…”
Section: Resultsmentioning
confidence: 99%
“…The exact mechanism through which these products provide benefits is being studied and may actually differ depending on the specific formulation. Mechanisms include modifying the pH of the gastrointestinal tract, production of antimicrobial or signaling molecules, competing for ecological niches and available nutrients, promoting epithelial cell differentiation and turnover, affecting mucus production, aiding in the metabolism of nutrients by the host, and/or stimulation of the immune system [13][14][15][16][17]. An exciting new perspective on intestinal/microbial symbiosis comes from the finding that pioneer colonizers, the first bacteria to reach the neonatal gut, can directly influence the development of the intestine and the nutrient matrix it provides for sequential bacterial species that eventually comprise the complex microbiota [18,19].…”
mentioning
confidence: 99%
“…Additionally, the bacteria present in the litter may influence the intestinal microbiota and performance of broilers (Cressman et al, 2010;Wei et al, 2013).…”
Section: Influence Of Covering Reused Broiler Litter With Plastic Canmentioning
confidence: 99%